Ane Mona and Hulda by Jenny Jordahl: a Feminist Didactic Perspectives on Children’s Literature - Hernández Quintana, Blanca (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This paper analyses the children’s story Ane Mona & Hulda by Jenny Jordahl, applying feminist didactics and hermeneutics proposed by feminist literary theory. By adopting this approach, we can gain insight into a different way of thinking that challenges heterocentrism and renders lesbianism visible. Furthermore, by altering the perspective of the conventional reading setting, we can uncover other discourses, such as  lesbianism, and thus critique the heterocentric bias. Within the feminist didactic approach, dialogue and reflection are the key methods, and reading is the medium that enables meaning-making. The conclusion is that, despite the imposition of heterosexuality as a norm by the homogenous social order that is reproduced by school and literature, the story provides the necessary resources to transform the experiential realm and reveal lesbianism as a natural orientation from an early age.